2010
DOI: 10.1186/1748-717x-5-96
|View full text |Cite
|
Sign up to set email alerts
|

Impact of residual and intrafractional errors on strategy of correction for image-guided accelerated partial breast irradiation

Abstract: BackgroundThe cone beam CT (CBCT) guided radiation can reduce the systematic and random setup errors as compared to the skin-mark setup. However, the residual and intrafractional (RAIF) errors are still unknown. The purpose of this paper is to investigate the magnitude of RAIF errors and correction action levels needed in cone beam computed tomography (CBCT) guided accelerated partial breast irradiation (APBI).MethodsTen patients were enrolled in the prospective study of CBCT guided APBI. The postoperative tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Cai et al reported the magnitude of residual-intrafractional errors in CBCT-guided supine partialbreast irradiation [29]. They found that even with 3 mm action level, the residual-intrafractional errors were similar to the skin marker set-up errors detected by pretreatment CBCT.…”
Section: Discussionmentioning
confidence: 82%
“…Cai et al reported the magnitude of residual-intrafractional errors in CBCT-guided supine partialbreast irradiation [29]. They found that even with 3 mm action level, the residual-intrafractional errors were similar to the skin marker set-up errors detected by pretreatment CBCT.…”
Section: Discussionmentioning
confidence: 82%
“…The details of patient position and CBCT imaging protocols have been reported in our previous study [16]. Briefly, all patients were fixed on the breast board and at a 200° arc (instead of 360°).…”
Section: Methodsmentioning
confidence: 99%
“…Prolonged treatment times and couch rotation can significantly reduce treatment delivery accuracy [44]. To address this confounder, patient surface setup systems and real time tracking systems have been recently explored.…”
Section: Newer Techniques For Breast Igrtmentioning
confidence: 99%